Synthesis and characterization of redox-active tris(pyrazolyl)borate cobalt complexes - David J. Harding (2018)
The reaction of CoX2 (X = Cl, Br, NO3) with KTp Ph2 in tetrahydrofuran (THF) yields the half-sandwich compounds [TpPh2CoX] (X = Cl 1, Br 2, NO33). The reaction of [TpPh2CoBr] with NaX (X = N3, NO2) or potassium thiocyanate (KNCS) permits isolation of [TpPh2CoX] (X = N 34, NCS 5, NO26). In contrast, the reaction of cobalt(ii) acetate with KTpPh2 yields [TpPh2Co(OAc)(Hpz Ph2)] 7 as a result of B-N bond cleavage. Subsequent reaction of 7 with a range of β-diketones in the presence of NaOMe produces the β-diketonate complexes, [TpPh2Co(β-diketonate)] (β-diketonate = acac 8, hfac 9, dbm 10, tmhd 11). IR spectroscopy suggests that the TpPh2 ligands are κ3-coordinated and that the β-diketonate ligands adopt a bidentate coordination mode. Electronic spectra are consistent with four- or five-coordinate species in solution. X-Ray crystallographic studies of 7 reveal an intermediate five-coordinate cobalt centre with a hydrogen bonding interaction between the pyrazole hydrogen and the acetate carbonyl oxygen. The molecular structures of 9 and 10 show cobalt centres with square pyramidal coordination geometries and κ2- coordinated β-diketonate ligands. Cyclic voltammetric studies of 6 reveal irreversible one-electron reduction to Co(i). However, the β-diketonate complexes, 8, 10 and 11 undergo irreversible one-electron oxidation. The redox potential and reversibility increases as the steric bulk of the substituent on the β-diketonate ligand increases. © 2009 The Royal Society of Chemistry.